2013
DOI: 10.1016/j.vaccine.2013.04.062
|View full text |Cite
|
Sign up to set email alerts
|

Increased IgG but normal IgA anti-pneumococcal protein antibodies in lung of HIV-infected adults

Abstract: PspA and pneumolysin (Ply) are important protein vaccine candidates. HIV infection is associated with increased susceptibility to pneumococcal pneumonia and concomitantly high pneumococcal carriage rates. Pneumococcal exposure is immunizing at the mucosa in healthy adults and so we wished to determine if the increased pneumococcal exposure in HIV-infected adults would be associated with altered pneumococcal specific antibody responses. We measured serum and bronchoalveolar lavage (BAL) fluid immunoglobulin (Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…However, previous studies have reported HIV-associated impairment of function of these two cell subsets in peripheral blood 1921 . Consistent with what has been observed in the systemic circulation, hyperglobulinemia has been reported in BAL fluid of HIV-infected adults 22, 23 , but the antibodies have impaired opsonic function 24 . It is plausible that the HIV-associated increase in B cells in the lung results in increased antibody production and BAL fluid hyperglobulinemia.…”
Section: Discussionsupporting
confidence: 81%
“…However, previous studies have reported HIV-associated impairment of function of these two cell subsets in peripheral blood 1921 . Consistent with what has been observed in the systemic circulation, hyperglobulinemia has been reported in BAL fluid of HIV-infected adults 22, 23 , but the antibodies have impaired opsonic function 24 . It is plausible that the HIV-associated increase in B cells in the lung results in increased antibody production and BAL fluid hyperglobulinemia.…”
Section: Discussionsupporting
confidence: 81%
“…Immunoglobulins in lung fluid can be derived from the blood by transudation or could be synthesized locally by cells within the lymphoid tissue in the respiratory tract. Furthermore, lung lining fluid antibodies are important in mucosal defense where the lungs are continually exposed to antigenic material, including during bacterial and viral infection (84)(85)(86). We detected both IgM and IgG SVV-specific antibodies in BAL fluid beginning at 10 dpi, which correlated with peak B cell proliferation and supports local secretion of antibodies.…”
Section: Discussionmentioning
confidence: 58%
“…Alveolar macrophages (AM) release GM-CSF and further induce the accumulation of macrophages and neutrophils in the lungs of HIV-infected subjects [114], and an increased amount of total and pneumococcal-specific Ab in the alveolar space [101, 115, 116]. However, due to the immune deficiency, opportunistic bacterial infections can create an inflammatory environment facilitating viral replication through up-regulation of cytokines and chemokines, which enhance HIV infection and replication, and perhaps promote viral egress from latent reservoirs [19, 117, 118]. HIV infection also impairs immune responses within the respiratory tract as well as M mannose receptor C-type lectin-mediated phagocytosis through the inhibition of Cdc42 and Rho activation, leading to a susceptibility of S. pneumonia infection in HIV infection [119].…”
Section: Introductionmentioning
confidence: 99%